Contrasting inequality in human exposure to greenspace between cities of Global North and Global South - Bin Chen; Shengbiao Wu; Yimeng Song; Chris Webster; Bing Xu; Peng Gong (Nature Communications, 2022)
Through an analysis of global differences in human exposure to greenspace, a new study identifies a contrasting pattern of greenspace exposure between Global South and North cities and finds seasonal variations in greenspace exposure inequality.